Tracking the Evolution in Phylogeny, Structure and Function of H5N1 Influenza Virus PA Gene. Issue 5 (5th December 2014) - Wei, K.; Lin, Y.; Li, Y.; Chen, Y.
Summary: Highly pathogenic avian influenza (HPAI) H5N1 viruses have severely affected the poultry industry of Vietnam and Indonesia. The outbreaks of HPAI H5N1 viruses continue to pose a serious threat to public health, which have profound impacts on public health. In this study, we presented phylogenetic evidences for five reassortants among HPAI H5N1 viruses sampled from Vietnam and Indonesia during 2003–2013 and found that reassortment events occurred more frequently in the three gene segments (PB1, PA and HA) than in the remaining five gene segments (PB2, NA, NP, NS and MP). The sequence‐based analyses have revealed that the PA protein displays high levels of DNA sequence polymorphism and variability than other internal proteins. Seven positive selection sites were detected in PA proteins, which ranked second only to the surface glycoproteins. Structure‐based comparative analysis of PA proteins showed a remarkable sequence conservation between the high‐pathogenic, low‐pathogenic and reassortant viruses, indicating that PA appears to be a potential antiviral target. Furthermore, by analysing the published data, we compared the differential expression of genes involved in RIG‐I‐ and MAVS‐mediated intracellular type I interferon (IFN)‐inducing pathway between the VN3028IIcl2‐infected, IDN3006‐infected and IDN3006/PA‐infected groups. Our analyses indicated that the inhibitory effect of the PA protein on MAVS was not strong. In addition, transcriptional levels of 33 mitochondrial proteins involved in the induction of apoptosis have significantly increased, suggesting that PA may play an important role in apoptosis signalling pathway.